Estimating the incidence of abortion: using the Abortion Incidence Complications Methodology in Ghana, 2017. Issue 4 (9th April 2020) - Polis, Chelsea B; Castillo, Philicia W; Otupiri, Easmon; Keogh, Sarah C; Hussain, Rubina; Nakua, Emmanuel K.; Larsen-Reindorf, Roderick; Bell, Suzanne O
Abstract : Introduction: Induced abortion is legally permitted in Ghana under specific conditions, but access to services that meet guidelines approved by government is limited. As part of a larger project comparing five methodologies to estimate abortion incidence, we implemented an indirect estimation approach: the Abortion Incidence Complications Methodology (AICM), to understand the incidence of abortion in Ghana in 2017. Methods: We drew a nationally representative, two-stage, stratified sample of health facilities. We used information from 539 responding facilities to estimate treated complications stemming from illegal induced abortions, and to estimate the number of legal abortions provided. We used information from 146 knowledgeable informants to generate zonal multipliers representing the inverse of the proportion of illegal induced abortions treated for complications in facilities in Ghana's three ecological zones. We applied multipliers to estimates of treated complications from illegal abortions, and added legal abortions to obtain an annual estimate of all induced abortions. Results: The AICM approach suggests that approximately 200 000 abortions occurred in Ghana in 2017, corresponding to a national abortion rate of 26.8 (95% CI 21.7 to 31.9) per 1000 women 15–49. Abortion rates were lowest in the Northern zone (18.6) and highest in the Middle zone (30.4). Of all abortions, 71% were illegal. Conclusion: Despite Ghana's relatively liberal abortion law and efforts to expand access to safe abortion services, illegal induced abortion appears common. A concurrently published paper compares the AICM-derived estimates presented in this paper to those from other methodological approaches.